Preclinical comparison study between [18F]fluoromethyl-PBR28 and its deuterated analog in a rat model of neuroinflammation. Issue 17 (15th September 2018) - Moon, Byung Seok; Jung, Jae Ho; Park, Hyun Soo; Contino, Marialessandra; Denora, Nunzio; Lee, Byung Chul; Kim, Sang Eun
Graphical abstract: The comparison studies of brain PET between [ 18 F]fluoromethyl-PBR28 ([ 18 F]1 ) and its deuterate analog ([ 18 F]1 - d 2 ) were investigated in the same LPS-induced neuroinflammation rat model as a novel translocator protein 18 kDa (TSPO)-targeted radioligand with enhanced in vivo stability. Highlights: Deuterated TSPO-binding ligand shows the enhanced in vivo metabolic stability. Deuterated analog maintains the biological potency of the parent. Enhanced stability leads to promoted target-to-background ratios of PET ligand. Abstract: We designed and synthesized deuterium-substituted [ 18 F]fluoromethyl-PBR28 ([ 18 F]1 - d 2 ) as a novel translocator protein 18 kDa (TSPO)-targeted radioligand with enhanced in vivo stability. The comparison studies between [ 18 F]fluoromethyl-PBR28 ([ 18 F]1 ) and its deuterate analog ([ 18 F]1 - d 2 ) were investigated in terms of in vitro binding affinity, lipophilicity and in vivo stability. In addition, the accuracies of both radioligands were determined by comparing the PET imaging data in the same LPS-induced neuroinflammation rat model. Both aryloxyanilide analogs showed similar lipophilicity and in vitro affinity for TSPO. However, [ 18 F]1 - d 2 provided significantly lower femur uptake than [ 18 F]1 (1.5 ± 1.2 vs . 4.1 ± 1.7%ID/g at 2 h post-injection) in an ex vivo biodistribution study. [ 18 F]1 - d 2 was also selectively accumulated in the inflammatory lesion with the binding potential of the specifically bound radioligand relative to the non-displaceable radioligand in tissue (BPND  = 3.17 ± 0.48), in a LPS-induced acute neuroinflammation rat model, comparable to that of [ 18 F]1 (BPND  = 2.13 ± 0.51). These results indicate that [ 18 F]1 - d 2 had higher in vivo stability, which resulted in an enhanced target-to-background ratio compared to that induced by [ 18 F]1 .